Early Growth Response Gene-2 Is Essential for M1 and M2 Macrophage Activation and Plasticity by Modulation of the Transcription Factor CEBPβ - Veremeyko, Tatyana; Yung, Amanda W. Y.; Anthony, Daniel C.; Strekalova, Tatyana; Ponomarev, Eugene D. (Frontiers in Immunology, 2018)
The process of macrophage polarisation is involved in many pathologies such as anti-cancer immunity and autoimmune diseases. Polarized macrophages exhibit various levels of plasticity when M2/M(IL-4) macrophages are reprogrammed into an M1-like phenotype following treatment with IFNγ and/or LPS. At the same time, M1 macrophages are resistant to reprogramming in the presence of M2-like stimuli. The molecular mechanisms responsible for the macrophages polarization, plasticity of M2 macrophages, and lack of plasticity in M1 macrophages remain unknown. Here, we explored the role of Egr2 in the induction and maintenance of macrophage M1 and M2 polarisation in the mouse in vitro and in vivo models of inflammation. Egr2 knockdown with siRNA treatment fail to upregulate either M1 or M2 markers upon stimulation, and the overexpression of Egr2 potentiated M1 or M2 marker expression following polarisation. Polarisation with M2-like stimuli (IL-4 or IL-13) results in increased Egr2 expression, but macrophages stimulated with M1-like stimuli (IFNγ, LPS, IL-6, or TNF) exhibit a decrease in Egr2 expression. Egr2 was critical for the expression of transcription factors CEBPβ and PPARγ in M2 macrophages, and CEBPβ was highly expressed in M1-polarised macrophages. In siRNA knockdown studies the transcription factor CEBPβ was found to negatively regulate Egr2 expression and is likely to be responsible for the maintenance of the M1-like phenotype and lack plasticity. During thioglycolate-induced peritonitis, adoptively transferred macrophages with Egr2 knockdown failed to become activated as determined by upregulation of MHC class II and CD86. Thus, our study indicates that Egr2 expression is associated with the ability of unstimulated or M2 macrophages to respond to stimulation with inflammatory stimuli, while low levels of Egr2 expression is associated with non-responsiveness of macrophages to their activation.